Resolvemos problemas aplicando la propiedad conmutativa de la adición - Ruiz Medina, Sara Angely (2019)
The present work of professional sufficiency develops the issue of commutative ownership in the sum of natural numbers, for which a learning design is presented based on the approach of solving quantity problems, currently in the area of curriculum for regular basic education, up to the practice of learning applications, matching them logically to solve them through strategies and thus developing the ability to solve specific problems from the classroom._x000D_ To this end, the first chapter presents the problematic reality, the objectives and the scientific justification or novelty. In the second chapter, the contextual cognitive and socio-partner theories that give foundation to pedagogical action are developed in depth. Finally, the third chapter, curriculum programming is developed, including general programming, specific programming, support materials, and process and unit evaluations. Thus, a concrete and complete programming is presented to develop the competencies of the students of the 3rd Grade in the area of Mathematics